Effective decision making and its impact on social justice:the Federal and Amhara National Regional Courts of Ethiopia - Shiferaw, Woubishet (2017)
This thesis examines the challenges that the Federal and Amhara National Regional State (ANRS)1 Courts of Ethiopia face in the realisation of legal and social justice. The Ethiopia Constitution (1995) under Article 43 declares that Ethiopian people have the right to improved living standards and sustainable development where the basic aim of development activity is to enhance, through their full participation, citizens’ capacity for development and the meeting of their basic needs. The Constitution underlined this as the ‘North Star’ of social justice which would be meaningless unless dispute resolution mechanisms empower litigants and the people in gaining social justice and thus the attainment of the Constitutional objective. The attainment of the social justice is however problematic as the legal justice the formal court is administering does not meet the people’s Constitutional expectations. The mismatch between legal and social justice, coupled with the legal history and the prevalence of justice pluralism, tends to force the People of Ethiopia to use non-formal systems of dispute resolution. Thus, there is a need to refine the formal and non-formal systems and to align them with the Constitutional imperative of social justice. Judicial reform is being implemented, with the help of international institutions like the World Bank, but the underlining concern is whether the World Bank proposals on judicial and legal reform will meet these needs or whether they are too located in Western values, the suggestion being that they may suffer from the same problems as other modernisation projects. There also lies a tension between the Constitutional expectation, the conceptualisation of justice by professionals and clients, and the overall purpose of securing justice and preventing injustice. Litigants’ preference for justice is itself in conflict with other litigants and the diverse institutional understanding of justice that made the attainment of social justice a difficult exercise. The area is found to be so problematic that there is a need to re-connect the practical conceptualisation of justice with the Constitutional conceptualisation of social justice which the Federal and ANRS courts require the redoing of justice so that the conceptualisation of justice would not cause irreversible damage to people’s societal, economic, and ecological demands and to the sustainability of justice and development.